Kekuatan Hukum Sertifikat Hak Atas Tanah Berdasarkan Prinsip Itikad Baik - I Nyoman Dirga (Jatiswara, 2017)
This research aims to know the menganalisi and land that is already dominated by the subject of the law for many years and has been completed with the certificate. But still there is no outside parties are demanding land rights. How did with prisif in good faith as set forth in militate crustaceans land. Sehinggan need to see land registry implementation procedures in order to obtain the power of the law of the strongest, according to the Government Regulation Number 24 in 1997, the power of legal land rights Certificates according to the provisions of article 32 paragraph (2) the Government Regulation Number 24 in 1997 and the accountability of the Agency which issued the Certificate of land rights over the land containing juridical defect. The approach used in this study is Statutes Approach, as is the provision of article 32 paragraph (2) Government Regulation No. 24 of 1997 about the land registry, conceptual approach related provision of article 32, paragraph (2) Go-vernment Regulation No. 24 of 1997 about land registry and Analitical approach based on the provisions of article 32 paragraph (2) the Government Regulation number 24 in 1997 about the land registry.